Exchange Rate Dynamics, Endogenous Risk Premium and the Balance Sheet Effect: An Effective Demand Model. (December 2018) - Basu, Moumita; Sengupta, Jonaki; Nag, Ranjanendra Narayan
This article describes a macroeconomic framework for analysing the interaction between output, domestic interest rate and exchange rate in the presence of the endogenous risk premium and balance sheet effect of exchange rate depreciation on investment demand. Output is demand determined. There are three assets: money, domestic bonds and foreign bonds. Domestic bonds and foreign bonds are not perfect substitutes due to the presence of risk premium. The endogenous risk premium depends on certain macroeconomic fundamentals, namely budget deficit and current account balance. Using this framework, we will examine implications of monetary policy, fiscal policy, tariff liberalization and global interest rate hike for exchange rate dynamics and output. The balance sheet effect and the risk premium together explain how an expansionary fiscal policy may generate recession, while tariff liberalization may produce favourable macroeconomic outcomes. Moreover, the model shows that an increase in world interest rate may have contractionary effect on the domestic output level due to the presence of the balance sheet effect of exchange rate depreciation. JEL Classification: E27, E63, F13, F32